Hypoxia-Inducible Lysine Methyltransferases: G9a and GLP Hypoxic Regulation, Non-histone Substrate Modification, and Pathological Relevance - Chopra, Anand; Cho, William C.; Willmore, William G.; Biggar, Kyle K. (Frontiers in Genetics, 2020)
Oxygen sensing is inherent among most animal lifeforms and is critical for organismal survival. Oxygen sensing mechanisms collectively trigger cellular and physiological responses that enable adaption to a reduction in ideal oxygen levels. The major mechanism by which oxygen-responsive changes in the transcriptome occur is mediated through the hypoxia-inducible factor (HIF) pathway. Upon reduced oxygen availability, HIF transcription factors activate hypoxia-responsive gene expression programs. However, under normal oxygen conditions, the activity of HIF is regularly suppressed by cellular oxygen sensors; prolyl-4 and asparaginyl hydroxylases. Recently, these oxygen sensors have also been found to suppress the function of two lysine methyltransferases, G9a and G9a-like protein (GLP). In this manner, the methyltransferase activity of G9a and GLP are hypoxia-inducible and thus present a new avenue of low-oxygen signaling. Furthermore, G9a and GLP elicit lysine methylation on a wide variety of non-histone proteins, many of which are known to be regulated by hypoxia. In this review we aim to review the effects of oxygen on G9a and GLP function, non-histone methylation events inflicted by these methyltransferases, and the clinical relevance of these enzymes in cancer.